ANALISIS PERAN MEDIA DIGITAL MARKETING SEBAGAI BRANDING SEKOLAH UNTUK PENINGKATAN MUTU PENDIDIKAN DI SD YPK IMANUEL KAMISABE KABUPATEN SORONG SELATAN - Winata, Wisnu; Komber, Mervin I.S.; Irwan, Andi (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the role of digital media as a marketing tool for school branding in improving the quality of education at YPK Imanuel Kamisabe Elementary School in South Sorong Regency. This study used a quantitative approach with an explanatory research design. The research objects were the use of digital media, school branding, and educational quality. The study population included parents, school committee members, and teachers, totaling 40 respondents, all of whom were sampled using a saturated sampling technique. Data collection was conducted through a closed-ended questionnaire with a Likert scale, while data analysis used descriptive statistics, the classical assumption test, the Pearson correlation test, and simple and multiple regression analyses to test the research hypotheses. The results showed that digital media had a positive and significant effect on educational quality, with a significance value <0.05, thus accepting the first hypothesis. School branding was also shown to have a positive and significant effect on educational quality, with a significance value <0.05, thus accepting the second hypothesis. Simultaneously, digital media and school branding had a significant effect on educational quality, with a significance value <0.05, thus accepting the third hypothesis. Research findings indicate that consistent use of digital media can strengthen a school's image, increase public trust, and drive improvements in educational quality, both in terms of the learning process and external support. The study's conclusions confirm that a digital media marketing strategy integrated with school branding is an effective and sustainable approach to improving educational quality, particularly in schools located in remote areas.